Asociación entre genotipos FTO (ns9939609) y marcadores de adiposidad en adultos chilenos (2018)
Background: Numerous studies have identified the role of Fat-mass-associated-gene (FTO) in the development of obesity. Aim: To investigate the association of FTO gene with adiposity markers in Chilean adults. Material and Methods: 409 participants were included in this cross-sectional study. The association between FTO (rs9939609) genotype and adiposity markers was determined using linear regression analyses. Adiposity markers included were: body weight, body mass index, fat mass, waist circumference, hip circumference and waist/hip ratio. Results: A fully adjusted model showed a significant association between FTO genotype and body weight (2.16 kg per each extra copy of the risk allele [95% confidence intervals (CI): 0.45 to 3.87], p = 0.014), body mass index (0.61 kg.m(-2) [95% CI: 0.12 to 1.20], p = 0.050) and fat mass (1.14% [95% CI: 0.39 to 1.89], p = 0.010). The greater magnitude of association was found between the FTO gene and fat mass when the outcomes were standardized to z-score. Conclusions: This study confirms an association between the FTO gene and adiposity markers in Chilean adults, which is independent of major confounding factors.